Dendritic cell derived IL‐2 inhibits survival of terminally mature cells via an autocrine signaling pathway. Issue 5 (18th March 2015) - Balachander, Akhila; Nabti, Sabrina; Sobota, Radoslaw M.; Foo, Shihui; Zolezzi, Francesca; Lee, Bernett T. K.; Poidinger, Michael; Ricciardi‐Castagnoli, Paola
<x xml:space="preserve">Abstract</x> DCs are crucial for sensing pathogens and triggering immune response. Upon activation by pathogen‐associated molecular pattern (PAMP) ligands, GM‐CSF myeloid DCs (GM‐DCs) secrete several cytokines, including IL‐2. DC IL‐2 has been shown to be important for innate and adaptive immune responses; however, IL‐2 importance in DC physiology has never been demonstrated. Here, we show that autocrine IL‐2 signaling is functional in murine GM‐DCs in an early time window after PAMPs stimulation. IL‐2 signaling selectively activates the JAK/STAT5 pathway by assembling holo‐receptor complexes at the cell surface. Using the sensitivity of targeted mass spectrometry, we show conclusively that GM‐DCs express CD122, the IL‐2 receptor β‐chain, at steady state. In myeloid DCs, this cytokine pathway inhibits survival of PAMP‐matured GM‐DCs which is crucial for maintaining immune tolerance and preventing autoimmunity. Our findings suggest that immune regulation by this novel autocrine signaling pathway can potentially be used in DC immunotherapy.